Configuration of systems for testing thermal imagers - Chrzanowski, Krzysztof; Li, Xianmin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Systems for testing thermal imagers offered commercially are built from the same modules: an off-axis reflective collimator, a motorized rotary wheel, a set of IR targets, a black body, a black body/wheel controller, a PC and some software. The classical solution is that all these components are located horizontally on an optical table. However, it is also possible to use a vertical configuration of the test system when the rotary wheel is put on the collimator and the black body is put on the rotary wheel. It was shown in this paper that when the vertical configuration is used, then better temporal stability and spatial uniformity of the thermal images projected by the test system can be achieved.
Optica Applicata, Vol. 40, 2010, nr 3, s. 727-735
Keywords: optyka; thermal imaging; infrared; metrology